The consumer revolution : tipping the balance of power - Nath, Naren (Sage, 2020)
"In this ground breaking book, Naren Nath provides a sweeping narrative of revolutions since the dawn of human civilization, leading up to the current and most impactful of them all--the consumer revolution. The book paints a gripping picture of consumers melding together, akin to nuclear fusion, to unleash unprecedented amount of energy and creativity, setting in motion a stunning transfer of power from traditional institutions. In doing so, it tosses up myriad new business ideas, and also highlights some of the sinister implications if the revolution is not harnessed correctly. The Consumer Revolution provides a fascinating context and rationale for some of the biggest current events and trends around the world. It is a stirring call for action to billions of everyday consumers to express their will and wield power in this ultimate doctrine of consumer empowerment"--Provided by publisher